Assessing ethical behavior of students in a Benedictine Medical School: developing an instrument - Conjares, Jesse Noel V.
This capstone project, titled "Assessing Ethical Behavior of Students in a Benedictine Medical School: Developing an Instrument," addresses the critical need for a tailored tool to systematically assess and provide feedback on the ethical conduct of medical students within institutions guided by specific moral traditions. Through an iterative development process that involved analyzing relevant ethical competencies and integrating the Ten Benedictine Hallmarks into observable behaviors, a comprehensive, behaviorally anchored instrument was created. This instrument features meticulously crafted descriptive anchors for both self-rating and observer rating scales, categorizing performance into levels of adherence, with corresponding scores such as "3 for Always Observed or Demonstrated," "2 for Sometimes Observed or Demonstrated," and "1 for Not Observed or Needs Guidance." The primary outcome is a two-part rating instrument providing behavioral descriptions across each Benedictine Hallmark, enabling targeted assessment and more precise feedback. Ultimately, this instrument is designed to facilitate objective assessment, foster meaningful self-reflection, and guide developmental efforts of the College of Medicine, thereby strengthening the ethical foundation of future medical professionals.